Rapid Monitoring of Bioaerosols from industrial, rural and urban environments - Garcia Alcega, Sonia; Coulon, Frederic; Tyrrel, Sean (Cranfield University, 2017)
•Sampling at constant flow rate and varying sampling time: - does not affect in presence/absence of MVOCs (70% similarity) - There is large difference in abundance (ng.m-3), (20% similarity). • Sampling at different flow rates and varying sampling time affects both peak detection and concentration.
Keywords: bioaerosol monitoring system'; 'Bioaerosols'; 'bioaerosol exposures'; 'Atmospheric Aerosols'